Wild bonobos host geographically restricted malaria parasites including a putative new Laverania species - Weimin Liu (Nature Portfolio, 2017)
Unlike chimpanzees and gorillas, bonobos have not been found infected by malaria parasites in the wild. Here, Liu et al. report more thorough survey and sequencing results showing that bonobos host malaria parasites, including a yet-unknown species, but only in the eastern-most part of their range.